Representing thyristor-controlled series capacitor and its control in PSCAD/EMTDC - 361202 Mohd. Noorazlan Fitri Md. Dali (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2003